Periódicos científicos eletrônicos: apresentação de modelo para análise de estrutura - Sarmento e Souza, Maria Fernanda [UNESP] (2002)
This paper presents the history and role of scientific communication, along with the changes that occurred after the appearance of electronic communication and computer networks. It describes the evolution and the archiving and dissemination functions of the scientific journal, the major tool for science communication. It introduces a ‘Model for analysis of the structure of electronic scientific journals’, with the aim of finding out if the basic functions are maintained in the electronic scientific journal. This model was developed based on studies dealing with: the evaluation of traditional journals; specific quality criteria for online journals; and the basic elements of web site information architecture, which should be considered when developing the page structure of electronic journals. This model also includes traditional structural elements from scientific journals adapted to the new media. The journals Ciência da Informação On-line and DataGramaZero were selected to validate this model. The results obtained include structure comparisons between a journal in transition from printed to electronic media (Ciência da Informação On-line) and an electronic journal (DataGramaZero), showing the structural elements that need to be kept in order to ensure maintenance of archival and dissemination functions. This study will contribute to the work of librarians, authors and users of scientific journals; to the identification of quality electronic journals; and to editors of on line journals in the development of their projects. The material obtained can be included in preservice and inservice Education of professionals in Information Science and support to editors of electronic scientific journals.